ANALISA IMPLEMENTASI MANAJEMEN RANTAI PASOK BERBASIS ERP PADA SISTEM DISTRIBUSI PT SEMEN INDONESIA TBK - Fidia; Peter Macnico; Julia Christini; Novi Sandra; Yuni Nuraeni; Nasar Buntu Laulita; Fendy Cuandra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
PT Semen Indonesia (Limited Company) is one of the largest companies in Indonesia that produces cement. The application of the ERP-based Supply Chain Management concept to the distribution system of PT Semen Indonesia is needed to fulfill the needs of end customers. This analysis aims to measure the performance of supply chain core processes in companies that have links ranging from the flow of raw materials from suppliers to the hands of final consumers, as well as ERP implementation in order to find out the positive and negative impacts of ERP implementation at PT Semen Indonesia in improving the distribution system. The research method used is qualitative by collecting related data and studies of documentation to map the ERP-based Supply Chain implementation at PT. Semen Indonesia, especially in the final product distribution process. The result achieved is to get a comparison between the positive and negative impacts of ERP implementation at PT Semen Indonesia in improving the distribution process. ERP implementation at PT Semen Gresik has a good impact on the effectiveness and efficiency of the distribution system improvement process, but also has consequences for the effectiveness and efficiency obtained. While the results of the analysis through business process modeling, the cement distribution process in the research object is included in the Supply Chain Operations Reference (SCOR) delivery process with the category of stocked product companies. Activities in the business process do not all follow the activities at SCOR, there is one activity that is not appropriate, namely providing proof of payment to customers, because the initial payment mechanism implemented by PT. Semen Indonesia.